Socio-cultural Management at Breksi Cliff: A Study Based on Sustainable Tourism Principles - Nihayati, Luluk; Supriyadi, Edouard Aryadi; Prasetyo, Andreas Yogi (Jurnal Manajemen Pelayanan Hotel, 2024)
As one of the areas in Yogyakarta that offers stunning natural attractions, Sleman has become a popular destination visited by many tourists. The progress of tourism development does have a positive influence on the economic sector, but if tourism management does not apply the principles of sustainable tourism, tourism development can actually have a negative impact on socio-cultural aspects. Based on its type, tourist destinations that are vulnerable to negative impacts on socio-cultural aspects are community-based tourism, Breksi Cliff is one of them. Breksi Cliff is a tourist destination in Sleman which has experienced significant growth in terms of the number of tourist visits, but there have been no studies examining whether tourism management in the socio-cultural aspect is aligned with the principles of sustainable tourism. Therefore, this study aims to find out whether the management of tourism in Breksi Cliff has applied UNWTO sustainable principles on socio-cultural aspects or not. The research method used is descriptive qualitative method. Research data were collected by conducting in-depth interviews and direct observation at the tourist destination. The results of the research show that most of the management of the socio-cultural aspects at Breksi Cliff is in accordance with indicators of sustainable tourism from UNWTO.